Applicability of the classic WACC concept in practice (2007)
A large percentage of companies use the discounted cash flow (DCF) approach as the primary technique for investment/project evaluation and the capital budgeting process. This approach requires forecasting the detailed cash flow of the project under evaluation and then discounting the resulting cash flow to the present value (Net Present Value-NPV) using an appropriate discount rate. The discount rate commonly used represents the Weighted Average Cost of Capital (WACC) of the firm. There is no scarcity of literature on this subject as the concept has been around for the last 50 years or so. Although most analysts believe the concept is simple and very well known, the irony is that its misinterpretation and misuse prevails. There are many versions of the WACC equation and each is specific to a certain cash flow. Therefore, using the classic WACC relationship in all cases may result in the calculation of an overly optimistic NPV. Depending on the cash flow pattern, the investment may show a positive NPV at the classic WACC but it will actually be losing equity. This paper highlights (a) pitfalls and misuses of the WACC, (b) interdependence between types of cash flow and WACC, (c) assumptions behind the WACC and whether these assumptions are realistic, and (d) alternative approaches to arrive at the correct net present value (NPV). Company CEOs, management, analysts, and other investors using the WACC for investment decisions need to be fully aware of its pitfalls and misuses. © 2007 by The Haworth Press.